Validation of a rapid test for HLA-B*58:01/57:01 allele screening to detect individuals at risk for drug-induced hypersensitivity. (April 2016) - Nguyen, Dinh Van; Vidal, Christopher; Li, Jamma; Fulton, Richard B; Fernando, Suran L
Aim: In prevention of allopurinol and abacavir hypersensitivity, screening HLA-B*58:01/57:01 has been highly recommended prior to commencing these therapies. Therefore, we aimed at developing and validating a rapid and robust screening method for HLA-B*58:01/57:01 .Materials & methods: Real-time polymerase chain reaction with TaqMan ® probes was employed to detect HLA-B*58:01/57:01 .Results: The newly developed assay has the sensitivity of 100% (95% CI: 79.4–100.0%), the specificity of 98.8% (95% CI: 93.6–99.9%), the positive predictive value of 94.1% (95% CI: 71.3–99.9%) and the negative predictive value of 100.0% (95% CI: 95.7–100.0%). The lowest limit of detection is 0.04 ng/µl of DNA.Conclusion: The present method is a rapid and robust assay that is appropriate for screening of HLA-B*58:01/*57:01 alleles.